2013
DOI: 10.5747/cv.2013.v005.n1.v074
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Da Ação Do Uso De Drogas Na Saúde Bucal De Dependentes Químicos

Abstract: The use ofdrugs of abuseis apublic health problem. One of thedifficulties intreatingdrug usersis thelack of informationon the subjectfacingdentistry.This study aimed toassessthe oral conditionsofaddicts in treatment in Centersfor Psychosocial Care (CAPS IIAD). We performedan interview, examinationof the oral cavity, sialometryassessmentandoralpHin 60patients attendingtwo CAPS IIADin twocitiesin the stateof SãoPaulo, of both sexesandover 18 years old. The majority(28%) were agedbetwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
19

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 23 publications
1
3
0
19
Order By: Relevance
“…26 In the present study, it was observed that the access to oral health services among the chemical dependents was almost exclusively for reasons of pain and/or dental extraction, in periods exceeding two years. These data are similar to the results found by O'Sullivan et al 27 and Alves et al 28 , noting that the search for emergency oral treatments were the main reasons for dental care. The negligence with self-care in health, low self esteem, the effects of licit and illicit substances on the periodontal tissues and reduced access to dental services are influential factors in the oral condition of drug users.…”
Section: Resultssupporting
confidence: 91%
“…26 In the present study, it was observed that the access to oral health services among the chemical dependents was almost exclusively for reasons of pain and/or dental extraction, in periods exceeding two years. These data are similar to the results found by O'Sullivan et al 27 and Alves et al 28 , noting that the search for emergency oral treatments were the main reasons for dental care. The negligence with self-care in health, low self esteem, the effects of licit and illicit substances on the periodontal tissues and reduced access to dental services are influential factors in the oral condition of drug users.…”
Section: Resultssupporting
confidence: 91%
“…Os indivíduos que apresentaram impacto das condições bucais na qualidade de vida tiveram 2,2 vezes mais chances de relatar dor de dente nos últimos seis meses. A população estudada se declarou insatisfeita com seu estado de saúde e qualidade de vida, no entanto, não foram encontradas associações entre a dor de origem dentária e a qualidade de vida geral, especificamente, embora muitos estudos afirmem que as condições bucais refletem diretamente na qualidade de vida [1][2][3]9 .…”
Section: Variávelunclassified
“…Quando se avaliou a possível associação entre a variável de estudo e o uso de cada substância não foram encontradas associações estatisticamente significantes, esse resultado vai ao encontro de um estudo realizado nos Estados Unidos, com 650 usuários de diversas substâncias, onde não foram encontradas associações significantes entre o uso da cada substância com a dor de dente, podendo ser resultado do uso associado de várias substâncias 15 . Se torna difícil relacionar as alterações bucais encontradas nos dependentes químicos com um tipo específico de substância, isso se deve principalmente ao fato dos indivíduos fazerem uso de várias substâncias ao mesmo tempo 9 .…”
Section: Variávelunclassified
See 1 more Smart Citation
“…Alves et al 5 , avaliaram as condições bucais de 60 dependentes químicos em tratamento em Centros de Atenção Psicossocial de duas cidades do interior do estado de São Paulo. Apenas 2% não possuíam nenhum dente permanente cariado, restaurado, perdido ou com extração indicada.…”
Section: Introductionunclassified